Investigação sobre a construção das noções espaço-geométricas por alunos da educação infantil - Paixão, Kelly Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research aims to understand how students of Early Childhood Education (considering the range of 2-3 years) build the space - geometric notions from the interaction established with the school routine. The venue was a municipal school Miners Tietê, within the State of São Paulo. The interest in this research took place from two reasons: the first because of course taken “Mathematics in Early Childhood Education” and the second stemmed from my professional work in a school for early childhood education. This research is initially composed by bibliographic studies concerning the topic and was grounded in a qualitative interpretive approach, aiming to investigate the psychological process of building space - geometric notions in children. The procedures used in the initial research to collect data were interviews using the method of clinical type and Piagetian tests. Thus allows us to understand the construction of the geometric space by children in their topological, projective and Euclidean relations

A presente pesquisa tem como objetivo principal compreender como os alunos de Educação Infantil (considerando a faixa dos 2 a 3 anos) constroem as noções espaço-geométricas, a partir da interação estabelecida com o cotidiano escolar. O local escolhido foi uma escola municipal de Mineiros do Tietê, no interior do Estado de São Paulo. O interesse em tal pesquisa deu-se a partir de dois motivos: o primeiro devido à disciplina cursada “Matemática na Educação Infantil” e o segundo adveio da minha atuação profissional em uma escola de Educação Infantil. Esta pesquisa inicialmente é composta pelos estudos bibliográficos do referente tema e embasa-se num enfoque qualitativo interpretativo, visando investigar o processo psicológico de construção das noções espaço-geométricas em crianças. Os procedimentos utilizados na referida pesquisa para a coleta de dados foram: entrevista segundo o método do tipo clínica e provas piagetianas. Deste modo, permite compreender a construção do espaço geométrico pelas crianças em suas relações topológicas, projetivas e euclidianas
Keywords: Epistemologia genetica; Espaços generalizados; Educação de crianças; Genetic epistemology